2011
DOI: 10.1080/19315864.2011.603881
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Psychopathology on the Pain Expression of Children and Youth With Intellectual and Developmental Disabilities

Abstract: Behavioral pain assessment is possible for children and youth with intellectual and developmental disabilities (IDD). However, pain behavior is often misinterpreted as reflecting psychopathology. We examined whether psychopathology alters pain behavior. Caregivers of 123 children (56 girls ages 40 to 258 months) completed the Non-Communicating Children's Pain Checklist-Revised (NCCPC-R) to assess pain behavior and the Diagnostic Assessment for the Severely Handicapped-II to assess psychopathology. Seventy-eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This model has since been corroborated by the findings of a few studies that, using mood induction, have demonstrated that lowering mood results in an increased rate of challenging behavior (Carr, McLaughlin, Giacobbe-Grieco, & Smith, 2003;Durand & Mapstone, 1998). Whilst Lowry's model is certainly more sophisticated than the arguably reductionist depressive equivalent approach, it does not account for other variables that could be acting as setting events for both depression and challenging behavior, such as pain, which research indicates has a clear association with both challenging behavior and low mood (Breau & Camfield, 2011;Carr & Owen-DeSchryver, 2007;Symons & Danov, 2005;Tervo, Symons, Stout, & Novacheck, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…This model has since been corroborated by the findings of a few studies that, using mood induction, have demonstrated that lowering mood results in an increased rate of challenging behavior (Carr, McLaughlin, Giacobbe-Grieco, & Smith, 2003;Durand & Mapstone, 1998). Whilst Lowry's model is certainly more sophisticated than the arguably reductionist depressive equivalent approach, it does not account for other variables that could be acting as setting events for both depression and challenging behavior, such as pain, which research indicates has a clear association with both challenging behavior and low mood (Breau & Camfield, 2011;Carr & Owen-DeSchryver, 2007;Symons & Danov, 2005;Tervo, Symons, Stout, & Novacheck, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…Little data regarding the pain reaction (chemical physiology) of people with intellectual disability during medical procedures are available (Phan et al, 2005). However, behavioural physiology identifies pain reaction of people with intellectual disability as a complex phenomenon (Breau and Camfield, 2011) with increased behavioural, emotional, conduct and inattention hyperactivity present (Oeseburg et al, 2010).…”
Section: Pain In the Context Of People With Intellectual Disabilitymentioning
confidence: 99%
“…Symons et al (2009) argues that pain behaviour appears to be associated with self-injury with implications for theories of the involvement of endorphins and as a casual factor and negates an elevated endorphin theory and indicates pain as a cause of self-injury. However, pain can also be the cause of self-injury (Breau and Camfield, 2011) and persons with intellectual disability experiencing chronic pain have been observed to self-injure near to the site of pain (Breau et al, 2003). Individuals with intellectual disabilities who self-injure demonstrate significantly more non-verbal behavioural signs of pain (Symons et al, 2009) and may show amplified pain expression (Defrin et al, 2004).…”
Section: The Concept Of Total Painmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that people with intellectual disability are at an increased risk of experiencing pain (Beacroft and Dodd, 2010; Blyth and Lee, 2011). Given the complex nature of pain (Faull et al, 2012), it follows that the management of pain for individuals with intellectual disability is challenging and frequently unaddressed or poorly addressed (Breau and Camfield, 2011; Massaro et al, 2013). This poor outcome is not surprising, given that in pain management communication and self-report is key (Findlay et al, 2014).…”
Section: Introductionmentioning
confidence: 99%